KEEFEKTIVAN PENGGUNAAN MEDIA REALIA TERHADAP HASIL BELAJAR IPA DI SEKOLAH DASAR - Cris Ayu Setyaningsih; Novia Rozanti; Galuh Andini; Taufik Hidayat (Jurnal Muara Pendidikan, 2019)
This study aimed to determine the effectiveness of the use of realia media on science learning outcomes in primary schools. The study was conducted using a quasi-experimental method with non equivalent control group design, by looking at the differences in pre-test and post-test between experimental and control class. The research subjects were students in fourth grade of SDN 2 Pringsewu Timur with class A as the experimental class and class B as the control class selected by cluster random sampling technique. Data analysis was performed through t-test, which was previously tested for normality and homogeneity prerequisites. The results showed that there were significant differences in learning outcomes between the experimental and control classes (significance level p = 0.006). Thus it can be concluded that the use of realia media is effective in improving science learning outcomes of students in fourth grade SDN 2 Pringsewu Timur.